Human umbilical cord mesenchymal stem cells accelerate and increase implant osseointegration in diabetic rats - Mefina KUNTJORO; Nike HENDRIJANTINI; Eric Priyo PRASETYO; Djoko LEGOWO; Ratri Maya SITALAKSMI; Bambang AGUSTONO; Muhammad Dimas Aditya ARI; Guang HONG (University of São Paulo, 2023)
Abstract Objective This study was conducted to assess the effect of hUCMSCs injection on the osseointegration of dental implant in diabetic rats via Runt-related Transcription Factor 2 (Runx2), Osterix (Osx), osteoblasts, and Bone Implant Contact (BIC). Methodology The research design was a true experimental design using Rattus norvegicus Wistar strain. Rattus norvegicus were injected with streptozotocin to induce experimental diabetes mellitus. The right femur was drilled and loaded with titanium implant. Approximately 1 mm from proximal and distal implant site were injected with hUCMSCs. The control group was given only gelatin solvent injection. After 2 and 4 weeks of observation, the rats were sacrificed for further examination around implant site using immunohistochemistry staining (RUNX2 and Osterix expression), hematoxylin eosin staining, and bone implant contact area. Data analysis was done using ANOVA test. Results Data indicated a significant difference in Runx2 expression (p<0.001), osteoblasts (p<0.009), BIC value (p<0.000), and Osterix expression (p<0.002). In vivo injection of hUCMSCs successfully increased Runx2, osteoblasts, and BIC value significantly, while decreased Osterix expression, indicating an acceleration of the bone maturation process. Conclusion The results proved hUCMSCs to accelerate and enhance implant osseointegration in diabetic rat models.